The art of game design : a book of lenses - Schell, Jesse (CRC Press/Taylor & Francis Group, 2015)
Presents the fundamentals of game design from one of the world's top game designers. Exploring the unusual territory that is game design, the book demonstrates how the basic principles of psychology used in board games, card games, and athletic games also work in top-quality video games. The author gives readers 100+ sets of insightful questions to ask themselves to make their games better. These questions provide insight from fields as diverse as psychology, architecture, music, visual design, film, software engineering, theme park design, mathematics, puzzle design, and anthropology.